Digital Transformation in Management Accounting: Implications for Strategic Decision-Making in Firms - Shujiro Urata (Journal of Business Innovation and Accounting Research, 2026)
Digital transformation has emerged as a pivotal force reshaping management accounting practices and strategic decision-making processes across global enterprises. This study investigates the implications of digital transformation on management accounting systems and their subsequent influence on strategic decision-making within Japanese firms. Drawing upon comprehensive analysis of existing literature and empirical evidence, this research examines how digital technologies are fundamentally altering traditional management accounting functions, including standard costing, performance measurement, and strategic planning processes. The findings reveal that digital transformation significantly enhances firms' financial performance through improved accounting information quality, operational efficiency, and decision-making capabilities (Chen & Zhang, 2024; . Furthermore, the study identifies that Japanese firms maintain distinctive approaches to management accounting practices, particularly in standard costing applications, which continue to evolve alongside digital transformation initiatives (Zoysa & Herath, 2007). The research demonstrates that strategic emphasis on digital transformation positively influences market capitalization and overall firm value, with implications varying based on organizational size and resource availability (Moker et al., 2020; . This investigation contributes to the understanding of how Japanese enterprises can leverage digital technologies to optimize management accounting practices while maintaining their traditional strengths in cost management and strategic planning. The study provides theoretical and practical insights for managers seeking to navigate the complexities of digital transformation in management accounting contexts.